Survivors [videorecording] - Dormer, Mike.; Fairley, John.; Welfare, Simon ([S.l.] Granite Production for Yorkshire Television, 1990)
Covers Nikita Khnushchen's rule in USSR freeing many Stalin's slaves and reforming the system. Deals with communists rejecting all Western influences.
VHS.
Credits : Narrator, Lian Phillips ; Editor, Martin Roche.
Keywords: Russia -- Politics and government; Russia -- Social conditions